Simulated annealing-backpropagation algorithm on parallel trained maxout networks in detecting credit card fraud. - Golingay,Sheila Mae D. (Quezon City University of the Philippines, 2019)
Abstract (Based on the Backpropagation (BP) artificial neural network algorithm, this study introduces the idea of combining Simulated Annealing (SA), a global searching algorithm and then proposes a new neural network algorithm: Simulated Annealing-Backpropagation Algorithm on Parallel Trained Maxout Networks (SABPMAX) algorithm. The proposed algorithm make use of the global searching capability of SA and the precise local searching element of the backpropagation algorithm to improve the initial weights of the network towards improving detection of credit card fraud. Several models were made and tested using different fraud distributions. Furthermore, separate applications of BP algorithm an SABPMAX algorithm were compared. Numerical results show higher accuracy rate, high sensitivity, shorter computing time, and overall better performance of the SABPMAX algorithm).
Thesis ( MS) --University of the Philippines